The effect of combined exercise (resistance-aerobic) valume on neurotrophic changes, neuropathic pain and some performance indicators in postmenopausal women with diabetic peripheral neuropathy - Tayebeh Amiri Parsa; Seyyed Reza Attarzadeh Hosseini; Nahid Bijeh; Mohammad Reza Hamedi Nia (Mashhad University of Medical Sciences, 2020)
Introduction:Diabetic neuropathy is one of the most common and severe complications of diabetes. Very few studies have investigated the effects of resistance-aerobic training on diabetic-peripheral neuropathy. This study was performed with aim to investigate the effect of combined exercise (Resistance - Aerobic ) on neurotrophic changes, neuropathic pain, aerobic endurance and lower body strength in postmenopausal women with diabetic peripheral neuropathy Methods: This practical and semi experimental study was performed on 21 patients with diabetic peripheral neuropathy in Sabzevar in 2017. The subjects were assigned into experimental and control groups. The experimental group performed resistance-aerobic exercises for four months. In fast condition, serum level of Brain-derived neurotrophic factor were taken before the start of the study and after the first, second, third and fourth months after the study. The neuropathic pain was measured with visual analog scale. Six-minute walking test (Rickly Jones) and sitting and standing test were used to estimate aerobic endurance and lower trunk performance, respectively. Data were analyzed by SPSS software (version 16) and Repeated Measure variance analysis and one-way ANOVA. PResults: Serum neurotrophin levels were not significantly increased in the experimental group compared to the control group (P> 0.05). Pain index significantly decreased compared to the control group (P< 0.05). Aerobic endurance and lower trunk functional strength significantly increased compared to the control group (P< 0.05). Conclusion: two months of combined exercise (Resistance - Aerobic ) reduces pain index and strengthens aerobic endurance and lower trunk functional strength. Probably, to increase serum neurotrophin levels, the training period should be longer than four months.